Reviewing the Post-2015 sustainable development goals and partnerships : a proposal for a Multi-level review at the High-level political forum - Beisheim, Marianne (2015)
Zusammenfassung: In September 2015, the heads of state and government of the United Nations Member States are scheduled to decide on the Post-2015 agenda. This is to include not only a list of universal Sustainable Development Goals (SDGs) but also a mechanism for monitoring and review. The High-Level Political Forum on Sustainable Development (HLPF) was launched in July 2013 to provide political leadership and guidance, and to work towards a global transformation to sustainable development. An important element of its work will be the review mechanism envisioned under the HLPF mandate, which is set to replace the Annual Ministerial Review (AMR) starting in 2016. What would the review mechanism have to look like to contribute to the implementation of sustainable development at all levels? A review process builds on and goes beyond monitoring and data collection. In this framework, the governments are asked critical, analytical questions to determine the reasons for their successes and failures, and to recommend measures needed to further improve goal attainment in the future. The present study examines the debate taking place over the review process, highlights the positions of selected key actors, discusses criteria for designing a review, and applies these to analyze and assess existing review systems. Finally, it develops specific proposals for a universal, state-led, participatory, multi-level "Commit and Review" process that could serve as a central component of the follow-up process for the Post-2015 agenda and goals. (SWP Research Paper)